ANGIOPLASTY UNTUK STENOSIS ATEROSKLEROSIS INTRAKRANIAL - Tranggono Yudo Utomo (Fakultas Kedokteran, Universitas Palangka Raya, 2021)
Intracranial atherosclerotic stenosis (ICAS) is a common cause of transient ischemic attack (TIA) and ischemic stroke which is the second – leading cause of death worldwide. At up to 40 – 50%, the rate of symptomatic ICAS is significantly higher in the Asian population and is probably the most common cause of stroke worldwide. Indication for endovascular treatment is a challenge and the selection of material as well as interventional techniques essentially differs from the treatment of extracranial stenosed. Conservative (medical and lifestyle change) and endovascular therapy procedures as well as endovascular therapeutic approaches (percutaneous balloon angioplasty (PTA) or stent – assisted angioplasty (PTAS) are available for the treatment of ICAS. This review aims to further evaluate the role of angioplasty in treating intracranial atherosclerosis. Endovascular treatment, such as balloon angioplasty with or without stenting, have emerged as therapeutic option for symptomatic intracranial stenosis. There are many types of endovascular techniques available for ICAS treatment, including balloon angioplasty alone, balloon – mounted stent (Pharos Vitesse), and self – expandable stent (Wingspan), each of which has its owns features and specific advantages relating to different intracranial artery lesion. Thus, endovascular treatment in ICAS patient is an alternative to prevent recurrent TIA/ischemic stroke. Endovascular treatment requires comprehensive considerations and multidiscipline team in order to provide effective treatment for ICAS patients.